The Effect of Education on Improving Adolescents’ Knowledge and Self Efficacy Regarding HIV/AIDS: A Pre-Experimental Study - Raden Bagus Edy Santoso; Wirda Wirda; Badariati Badariati; Hasnidar Hasnidar; Dina Palayukan Singkali (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
Background: HIV/AIDS remains a growing global health concern, including among adolescents. Low knowledge and inadequate self-efficacy related to HIV/AIDS prevention are major risk factors for risky behaviors in adolescents. School-based education is considered an effective strategy to enhance adolescents’ awareness and capacity to prevent HIV/AIDS. Objective: This study aimed to analyze the effect of HIV/AIDS educational intervention on the knowledge and self-efficacy of adolescents at SMAN Negeri 3 Palu. Methods: This study employed a one-group pretest–posttest design. The sample consisted of 61 eleventh-grade students selected purposively. Research instruments included an HIV/AIDS knowledge questionnaire (20 items) and a self-efficacy scale (15 statements, Likert scale 1–5). Data were anayzed using the Mann–Whitney test to assess differences between pretest and posttest scores. Results: The findings indicated a significant increase in knowledge (pretest mean = 32.01, posttest mean = 90.99, p < 0.05) and self-efficacy (pretest mean = 42.6, posttest mean = 57.3, p < 0.05) following the educational intervention. These results suggest that school-based education effectively enhances adolescents’ understanding of HIV/AIDS and their confidence in implementing preventive measures. Conclusion: School-based HIV/AIDS education can improve adolescents’ knowledge and self-efficacy, which are critical prerequisites for safer HIV preventive behaviors. This study recommends the development of ongoing educational programs in schools, the involvement of peer educators, and further research employing controlled designs with long-term behavioral evaluations.